2001
DOI: 10.1038/sj.leu.2402124
|View full text |Cite
|
Sign up to set email alerts
|

Elevated vascular endothelial growth factor (VEGF) serum levels in idiopathic myelofibrosis

Abstract: An increase of angiogenesis has been shown in idiopatic myelofibrosis with myeloid metaplasia (MMM) by microvessel density count method but evaluation of circulating angiogenic factors is still incomplete. In 31 patients affected by MMM and in 12 healthy subjects we evaluated the serum levels of VEGF (vascular endothelial growth factor) and correlated VEGF with clinical and laboratory features of disease. We found that MMM patients had circulating VEGF concentrations much higher than controls (median 1208 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 30 publications
1
57
0
3
Order By: Relevance
“…32 In addition, MKs also synthesize vascular endothelial growth factor and thrombospondin, 2 cytokines that are able to stimulate the bone marrow angiogenesis associated with the myelofibrosis. 33 However, the mechanisms that lead to the release of these cytokines by MKs in the marrow environment are poorly understood. It has been suggested that this was due (1) to dysplastic MKs that die in the marrow, 5 (2) to cell death induced by polymorphonuclear cells after their emperipolesis by MKs, 34,35 or (3) to a spontaneous release of the MK ␣-granule content.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, MKs also synthesize vascular endothelial growth factor and thrombospondin, 2 cytokines that are able to stimulate the bone marrow angiogenesis associated with the myelofibrosis. 33 However, the mechanisms that lead to the release of these cytokines by MKs in the marrow environment are poorly understood. It has been suggested that this was due (1) to dysplastic MKs that die in the marrow, 5 (2) to cell death induced by polymorphonuclear cells after their emperipolesis by MKs, 34,35 or (3) to a spontaneous release of the MK ␣-granule content.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why FGF-2 concentrations in marrow aspirates and peripheral blood correlate with MM activity (Di Raimondo et al, 2000;Sezer et al, 2001;Sato et al, 2002). Bisping et al (2003) have illustrated the expression of highaffinity FGFR-1 through R-4 in RPMI-8226 and U266 MM cell lines and patients' plasma cells, as well as in BMSC, and hence the likelihood of both autocrine and paracrine loops of growth and angiogenesis.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…27,29 A recent report has shown that expression of VEGF is restricted to myeloblasts and immature myeloid elements in various MDS subtypes 30 and VEGF has been found to be elevated in patients with idiopathic myelofibrosis. 31 Furthermore, in a series of 99 patients with newly diagnosed AML, Aguayo et al 32 found that increased cellular VEGF is an independent poor prognostic factor in patients with AML. VEGF type C, another member of the vascular endothelial growth factor family, is expressed by leukemic blasts in a significant proportion of patients with AML.…”
Section: Introductionmentioning
confidence: 99%